REORIENTASI KEBIJAKAN PEMIDANAAN BAGI PENYALAHGUNA NARKOTIKA - Setiyono Setiyono (Jurnal Cakrawala Hukum, 2016)
Narcotics abuse is a felony offense which is punishable by criminal sanctions. A sentencing policy againstnarcotics abusers regardless of the position of the abuser as an offender or victim may have a negative impacton the coaching process for the abuser itself. In this case, it is necessary to reorient the policy of sanctions againstnarcotics abusers based on the basic idea and purpose of sanctions for narcotics abusers. Such a policy is ademanding situation and condition that can uphold the dignity of the narcotics abuser in society. Therefore,the policy of criminal sanctions in the Narcotics Act needs are depenalization or to be changed into treatmentsanction. Depenalization of criminal sanctions against narcotics abusers can be done through the policy ofnarcotics abusers rehabilitation both medically and socially so that they can escape from narcotic dependencyand can resocialize with the community.